2014
DOI: 10.1097/bpb.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

Medial patellar subluxation without previous lateral release

Abstract: Medial patellar subluxation (MPS) is normally described following a lateral release. We report on a 14-year-old girl with MPS without previous lateral release. Arthroscopic examination demonstrated MPS at 0 and 30° of flexion, and the patella was tight in flexion on the lateral side. A low lateral release with a tibial tubercle transfer was performed, followed by repair of the lateral release with an iliotibial band flap, and lateral patellofemoral ligament reconstruction. Excellent functional outcome was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…23 Several case series of noniatrogenic medial patellar instability have also been reported in the literature, but they are few in number. 1,13,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Several case series of noniatrogenic medial patellar instability have also been reported in the literature, but they are few in number. 1,13,17 …”
Section: Discussionmentioning
confidence: 99%
“…23 Several case series of noniatrogenic medial patellar instability have also been reported in the literature, but they are few in number. 1,13,17 In cases where iatrogenic medial patellar instability is suspected, it has been recommended that patients should undergo a 6-week trial of a supervised reverse McConnell taping so that the diagnosis can be confirmed and also as a prognostic factor of symptom relief by potential surgery. 18 Several techniques have been described to repair or reconstruct the lateral retinacular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Other cases of noniatrogenic medial patellar instability in the literature typically present as chronic subluxations. These cases display medial patellofemoral tracking and have been treated using various methods, including nonoperative treatments (eg, physical therapy) and operative treatments (eg, quadricepsplasty with lateral retinacular imbrication, 16 lateral retinacular and lateral patellofemoral ligament reconstruction, 2,18 and medial retinacular release 19 ). Additionally, there is a subset of patients with noniatrogenic medial patellar instability with syndromic features that contribute to instability.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited literature describing isolated or spontaneous MPS in the absence of a previous lateral release [7] [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited literature describing traumatic and isolated MPS in the absence of a previous lateral release [7] [8]. We report a case of medial subluxation following minor trauma that was demonstrated by magnetic resonance imaging (MRI) and successfully treated by direct repair of the lateral retinaculum.…”
Section: Introductionmentioning
confidence: 99%